Heparin binding preference and structures in the fibroblast growth factor family parallel their evolutionary diversification - Yong Li; Changye Sun; Edwin A. Yates; Chao Jiang; Mark C. Wilkinson; David G. Fernig (Open Biology, 2016)
The interaction of a large number of extracellular proteins with heparan sulfate (HS) regulates their transport and effector functions, but the degree of molecular specificity underlying protein–polysaccharide binding is still debated. The 15 paracrine fibroblast growth factors (FGFs) are one of the paradigms for this interaction. Here, we measure the binding preferences of six FGFs (FGF3, FGF4, FGF6, FGF10, FGF17, FGF20) for a library of modified heparins, representing structures in HS, and model glycosaminoglycans, using differential scanning fluorimetry. This is complemented by the identification of the lysine residues in the primary and secondary binding sites of the FGFs by a selective labelling approach. Pooling these data with previous sets provides good coverage of the FGF phylogenetic tree, deduced from amino acid sequence alignment. This demonstrates that the selectivity of the FGFs for binding structures in sulfated polysaccharides and the pattern of secondary binding sites on the surface of FGFs follow the phylogenetic relationship of the FGFs, and so are likely to be the result of the natural selection pressures that led to the expansion of the FGF family in the course of the evolution of more complex animal body plans.